2016
DOI: 10.3390/ijms17111940
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatin-TL1, an Anti-Inflammatory Active Peptide from the Venom Gland of Hydrophis cyanocinctus in the South China Sea

Abstract: Tumor necrosis factor (TNF)-α is a pleiotropic cytokine with intense pro-inflammatory and immunomodulatory properties, and anti-TNF-α biologics are effective therapies for various inflammatory diseases such as inflammatory bowel disease (IBD) and sepsis. Snake venom, as a traditional Chinese medicine, has been used in the treatment of inflammatory diseases in China for centuries. In this research, we constructed a venom gland T7 phage display library of the sea snake Hydrophis cyanocinctus to screen bioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Hydrostatin, as a bioactive peptide extracted from snake poison, was reported to inhibit inflammatory responses [8, 23]. However, little is known about its effect on pancreatitis-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrostatin, as a bioactive peptide extracted from snake poison, was reported to inhibit inflammatory responses [8, 23]. However, little is known about its effect on pancreatitis-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“… Altmann et al (2012) found serum IL-6 produced by circulating monocytes would stimulate alveolar macrophage production of CXCL1, leading to neutrophil recruitment and lung injury. Thus, numerous investigators have reported that inhibiting the overproduction of TNF-α, IL-6, and IL-1β cytokines can alleviate lung injury ( Nonas et al, 2006 ; Hirano et al, 2015 ; Wang et al, 2016 ). In the present study, our in vivo and in vitro experiments both demonstrated that H-SN1 could significantly alleviate the LPS-induced increase in the expression and release of TNF-a, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, phage display represents a more economical and effective option to select specific peptide ligands that interact with inflammatory mediators [13,14]. For instance, two peptides of Hydrostatin-SN1 [15] and Hydrostatin-TL1 [16] with anti-inflammatory activity have been screened out from the phage display peptide library generated on the toxins of the sea snake. Both peptides can specifically bind to TNFR1 and inhibit its downstream pathways, resulting in an anti-inflammatory effect.…”
Section: Of 12mentioning
confidence: 99%